Giant mandibular osteoma, CT findings for the primary care provider - Rajaram Sharma; Amit Kumar Dey; Prasad Udmale; Aditi Priyamvara; Shah Alam; Debashish Dey; Hemangini Thakkar (Journal of Family Medicine and Primary Care, 2023)
We report a very rare case of 35-year-old female with a giant mandibular osteoma in the angle of the mandible. We highlight the importance of CT in diagnosing as well as defining the extent of this rare case so that proper management can be undertaken. We also showcase the importance of angiography to show relationship of this mass with the surrounding vessels.